Pengembangan AMPURASIA: media interaktif berbasis aplikasi android pada materi teks puisi rakyat kelas VII SMP - Wijayanti, Citra Putri; Sulistiyono, Roni (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
Android-based learning media has become one of the innovations in 21st-century education. There is a need for new educational technologies aligned with the current demands and challenges of learning, especially in preparing for PISA and AKM assessments. This article describes the development and feasibility testing of the Android-based application 'AMPURASIA' as a learning medium for 7th-grade junior high school students on traditional poetry texts. The research follows the R&D approach, using the Borg & Gall model, which involves seven essential stages: (1) data collection, (2) product design planning, (3) initial product development, (4) limited-scale preliminary testing, (5) initial product revision, (6) field testing, and (7) final product revision. This study employed observation sheets and questionnaires as data collection instruments. In the limited trial, the researcher involved 10 students as subjects, while experts served as validators. The data collected were analyzed using descriptive quantitative methods. The analysis results showed that the learning media was rated 'highly feasible' with an average score of 88% on the product feasibility test. Therefore, the product can be utilized as an interactive learning medium.